2013
DOI: 10.1007/s13277-013-1018-2
|View full text |Cite
|
Sign up to set email alerts
|

CARMA3 is overexpressed in human glioma and promotes cell invasion through MMP9 regulation in A172 cell line

Abstract: Caspase recruitment domain-containing membrane-associated guanylate kinase protein 10 or CARMA3 (CARD10) is a recently characterized oncoprotein involved in the progression of several human malignancies. The present study aims to investigate the expression pattern and biological roles of CARMA3 protein in human glioma. CARMA3 expression was analyzed in 97 glioma specimens using immunohistochemistry. We observed negative staining in normal astrocytes and positive staining of CARMA3 in 25 out of 97 (25.8%) gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Matrix metalloproteases (MMPs) are important in tumor growth, invasion and metastasis (15). Studies have shown that matrix metallopeptidase 9 (MMP-9), one of the most important MMPs, functioned in the migration, invasion and metastasis of numerous types of cancer, including CRC, through various signaling pathways (16)(17)(18)(19)(20)(21)(22)(23). MMP-9, activated by astrocyte elevated gene-1 (24), ERK-dependent induced MMP-9 (25) and the p38-MMP-9 pathway (26), increases the invasiveness of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteases (MMPs) are important in tumor growth, invasion and metastasis (15). Studies have shown that matrix metallopeptidase 9 (MMP-9), one of the most important MMPs, functioned in the migration, invasion and metastasis of numerous types of cancer, including CRC, through various signaling pathways (16)(17)(18)(19)(20)(21)(22)(23). MMP-9, activated by astrocyte elevated gene-1 (24), ERK-dependent induced MMP-9 (25) and the p38-MMP-9 pathway (26), increases the invasiveness of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-9 mRNA expression was found to correlate with colorectal cancer cell invasion, indicating that the inhibitory effect of miR-195 on colorectal cancer cell invasion may at least partially be mediated through the downregulation of MMP-9, by directly targeting CARMA3. In accordance with these findings, Feng et al (15) reported that CARMA3 promoted glioma cell invasion through upregulating the expression of MMP-9.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, Feng et al (15) reported that CARMA3 promoted glioma cell invasion through MMP-9, a key tumor invasion factor. Thus, to investigate the mechanism by which miR-195 regulates colorectal cancer cell invasion, MMP-9 mRNA expression was assessed in each group.…”
Section: Mir-195 Inhibits Colorectal Cancer Cell Invasion Through Tarmentioning
confidence: 99%
“…Furthermore, CARMA3 knockdown in breast cancer cells with high endogenous CARMA3 resulted in increased paclitaxel-induced apoptosis, while overexpression of CARMA3 resulted in enhanced proliferation and reduced apoptosis, results which suggested a role for CARMA3 in chemotherapeutic resistance ( 124 ). In glioma patient tumor specimens, 26% of samples showed CARMA3 overexpression relative to normal astrocytes in the same specimen ( 125 ); the authors also showed that CARMA3 knockdown in a glioma cell line suppresses cell invasion in vitro and results in decreased expression of MMP9, a matrix metalloprotease closely linked with tissue invasion. These results suggested a possible mechanism by which C3BM signaling promotes invasion in human glioma.…”
Section: Other Studies Of Carma3 In Solid Tumorsmentioning
confidence: 99%